2019
DOI: 10.1371/journal.pone.0213793
|View full text |Cite
|
Sign up to set email alerts
|

Dengue seroprevalence among asymptomatic blood donors during an epidemic outbreak in Central-West Brazil

Abstract: Dengue virus (DENV) transmission by blood transfusion is an important route of viral acquisition during outbreaks. The prevalence of DENV markers (viral RNA, NS1, anti-DENV IgM, and IgG) among blood donors in Central-West Brazil has never been evaluated. Our aim was to evaluate the full set of serological and molecular markers for DENV among blood donors of the Federal District of Brazil during an extensive outbreak in 2016. We found an anti-DENV IgM prevalence of 6.74% (n = 32/475). Of 475, 20 samples (4.21%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…We observed a prevalence of 16 % of anti-DENV IgM. In 2016, the prevalence observed in the same region for anti-DENV IgM was 6.7 % [8]. In 2019, the Federal District of Brazil had 47 393 probable cases of DENV, according to the Epidemiological Surveillance Bulletin, versus 24 019 probable cases of DENV in 2016.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…We observed a prevalence of 16 % of anti-DENV IgM. In 2016, the prevalence observed in the same region for anti-DENV IgM was 6.7 % [8]. In 2019, the Federal District of Brazil had 47 393 probable cases of DENV, according to the Epidemiological Surveillance Bulletin, versus 24 019 probable cases of DENV in 2016.…”
Section: Discussionmentioning
confidence: 90%
“…In a previous study, we evaluated the prevalence of DENV markers in blood donors during an outbreak in the Federal District of Brazil in 2016 [8]. In this study, we re-evaluated some DENV markers in a representative number of blood donors during the outbreak of 2019, the largest outbreak after 2016 to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might have contributed to the lower number of asymptomatic infections in blood donors and a negative PCR result in our study. During the study period, a higher DENV circulation was also reported as evaluated by the high anti-DENV IgM prevalence detected among blood donors, 11 an infection which might have played a prominent role during the study period. Our results may also mean that when our study took place, the ZIKV outbreak may not have fully affected the Federal District of Brazil, thus differing from the ZIKV outbreaks reported in Southeast and Northeast Brazil.…”
mentioning
confidence: 79%
“…people tested after onset of symptoms, and therefore ignores the characteristics and patterns of dengue infections (ascertained from a serosurveillance campaign by Li and colleagues ( Li et al., 2019 )). In fact, a great proportion of infections are likely to be asymptomatic ( Slavov et al., 2019 ) and the incidence of dengue cases doesn't necessarily correlate with the underlying transmission intensity ( Perkins et al., 2014 ). In addition, we cannot unrealistically assume that all the infections originated at household location/proximity without considering other important variables that may have played a role in the geographic ranges of dengue transmission, such as house quality and socioeconomic conditions ( Farinelli et al., 2018 ; Lippi et al., 2018 ) or human behaviour and mobility (shopping, schooling for example)( Stoddard et al., 2013 ; Chuang et al., 2018 ; Kraemer et al., 2018 ; Sanna et al., 2018 ; Wen et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%